Statement of Gardiner Spring - Spring, Gardiner, 1785-1873.
Statement regarding the licensure of Benjamin Chase as a Presbyterian clergyman.
Presbyterian clergyman.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Chase, Benjamin, -- 1789-1870.; Presbyterian Church -- Clergy; Clergy